Preoperative factors and four-year decompressive laminectomy success in symptomatic lumbar spinal stenosis - Fields, Daryl P.; Holloway, Kathryn Lois; Levin, Emily; Keyserling, Harold; Nortman, Samuel; Krein, Sarah L.; Gentili, Amilcare; Katz, Jeffrey N.; Perera, Subashan; Weiner, Debra K. (Frontiers in Musculoskeletal Disorders, 2025)
Background/context Decompressive laminectomy (DL) for lumbar spinal stenosis (LSS) is the most common spinal surgery for older adults. Biopsychosocial factors are associated with 1-year outcomes in these patients. While most surgical failures occur within 12 months, some are delayed, and factors responsible for delayed surgical failure are poorly understood. Purpose We sought to identify preoperative factors associated with long-term surgical success as defined by the Brigham Spinal Stenosis (BSS) questionnaire. Study design/setting/patient sample Within this prospective cohort study, we used logistic regression modeling to identify preoperative biopsychosocial factors that predict 4-year DL success in 110 prospectively evaluated veterans who underwent DL without fusion for LSS. Outcome measures/methods A questionnaire was used to evaluate BSS outcomes at 4 years post-DL. Results Overall, 69 participants (63%) demonstrated 4-year surgical success—sustained improvement in at least two of the three BSS domains (symptoms, function, and satisfaction). Greater catastrophizing [OR for 2 points 0.92 (0.84–1.00); p = 0.0512] and longer symptom duration [OR for 12 months 0.96 (0.93–0.99); p = 0.0231] were associated with lower likelihood of success, while presence of moderate/severe stenosis (OR 7.16–7.39; p = 0.0195–0.0260), college education [OR 2.93 (1.27–6.77); p = 0.0120], and greater treatment credibility [OR for 10 points 1.35 (1.10–1.66); p = 0.0048] were associated with greater likelihood of success in bivariate analyses. Symptom duration [OR 0.96 (0.92–0.99); p = 0.0208], treatment credibility [OR 1.51 (1.15–1.98); p = 0.0031], and stenosis severity (OR 14.4–17.4; p = 0.0045–0.0055) constituted a parsimonious set of factors in multivariable modeling. Conclusions Further work is needed to definitively identify preoperative factors that predict long-term outcomes. This may facilitate more accurate patient selection and counseling for patients undergoing DL for LSS.